Research progress on sequential immunization strategies of COVID-19 vaccines: a review - Rongrong DAI; Hangjie ZHANG; Jianmin JIANG (Editorial Office of Chinese Journal of Public Health, 2024)
The global pandemic of the coronavirus disease 2019 (COVID-19) has had a serious impact on global life safety and economic development. Vaccination with the coronavirus disease vaccine (COVID-19 vaccine) is an important measure to prevent infection, reduce the incidence and severity of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Currently, there are six different technological routes for COVID-19 vaccines worldwide, including protein subunit vaccines, nucleic acid vaccines (mRNA vaccines and DNA vaccines), viral vector vaccines, inactivated vaccines, virus-like particle vaccines, and attenuated vaccines. Sequential immunization strategy is a valid approach for solving vaccine shortages, responding to viral variants, and improving vaccine efficacy by administering COVID-19 vaccines of different technological routes at specific time intervals and doses. Many scholars at home and abroad have conducted research on the sequential immunization strategy of COVID-19 vaccines. This article provided an overview of the research on the sequential immunization strategy of COVID-19 vaccines at home and abroad in five aspects: COVID-19 inactivated vaccine and mRNA vaccine, COVID-19 inactivated vaccine and adenovirus vector vaccine, COVID-19 inactivated vaccine and protein subunit vaccine, COVID-19 adenovirus vector vaccine and mRNA vaccine, COVID-19 adenovirus vector vaccine and protein subunit vaccine, aiming to provide reference for the inoculation and formulation of immunization strategies for COVID-19 vaccines.